Is there an easy way to solve a system like this one?
x y/(3x-4y)=2/11
y z/(2y+3z)=6/5
x z/(x-z)=3/2
Luke
These are the same, assuming that none of x, y, and z is zero.the first eqn is the same as:
(1/x)+(1/y)=3/8 (1)
the second eqn is:
(1/y)+(1/z)=5/8 (2)
the third eqn:
(1/x)+(1/z)=6/8 (3)
The same process would likely work.Can one transform the three equations into the 1/x + 1/y form like in the previous example?
As mentioned previously, "The same process would likely work." That means that the same sort of transformation likely can also be done with the posted system. So try it, and see what happens!I know that : x y /(x+y) = 8/3 is the same as 1/x + 1/y = 3/8
Could this sort of transformation also be done with: x y / (3x - 4y) = 2/11 ?